189k views
0 votes
Fill in the quadratic formula below using the equation above.

Fill in the quadratic formula below using the equation above.-example-1

1 Answer

3 votes

Given a quadratic equation with the following form


y=ax^2+bx+c

The quadratic equation is


x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

The equation given is


y=x^2-5x-14

Our coefficients are


\begin{gathered} a=1 \\ b=-5 \\ c=-14 \end{gathered}

Rewritting the quadratic formula using those values, we have:


x=\frac{-(-5)\pm\sqrt[]{(-5)^2-4(1)(-14)}}{2(1)}

User UiUx
by
5.2k points